Isozyme Variation and Genetic Relationships among Three Plumbago Species - T. Renisheya Joy Jeba Malar2, M. Johnson1*, A. Usha Raja Nanthini2 and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-bidi-font-weight: bold; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The purpose of the study is to understand the genetic affinities and variation among three Plumbago species by means of isoenzyme viz., esterase, peroxidase, poly phenol oxidase and Restriction Fragment Length Polymorphism using Eco RI, Hind III and Bam HI. Each and every species expressed their similarities and variation by the presence and absence of their banding profiles in the gel system. A total of 32 bands were observed in the isozyme system of Plumbago species.<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> The RFLP profile of the Plumbago species showed seven bands in three active zones / regions. The cladogram shown that two clusters, of which cluster 2 includes only one species viz., P. auriculata showed 100% of divergence with other two species. Cluster 1 (C1) showed two nodal (N) branches (C1N1 and C2N2). C1N1 was P. zeylanica and C1N2 was P. rosea.